1999
DOI: 10.1136/pgmj.75.888.611
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous glucagon in severe tricyclic poisoning

Abstract: A case of dothiepin poisoning complicated by cardiogenic shock is described. Hypotension was resistant to conventional inotropes but responded rapidly to high-dose intravenous glucagon. Glucagon should be considered as a useful therapeutic positive inotrope and a potentially antiarrhythmic agent in severe tricyclic antidepressant overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Recent experimental studies have shown that many agents, such as L-NAME, a nitric-oxide synthase inhibitor, selective adenosine A 1 and A 2a receptor antagonists, and glucagon, are effective in reversing TCA-induced hypotension (Kalkan et al, 2004;Pentel et al, 1996;Tuncok et al, 2002;Kaplan et al, 2008). There are case reports suggesting the beneficial effects of vasopressin and glucagon in TCA overdose (Sensky and Olczak, 1999;Downes, 2003;Barry et al, 2006). Heard et al showed that TCA antibody fragments (TCA Fab) raise total serum TCA levels while lowering free levels in TCA-poisoned patients and no toxic effects were associated with the increase in TCA levels, but in this study, there were no significant changes in QRS duration, HR, or MAP associated with the Fab infusion (Heard et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Recent experimental studies have shown that many agents, such as L-NAME, a nitric-oxide synthase inhibitor, selective adenosine A 1 and A 2a receptor antagonists, and glucagon, are effective in reversing TCA-induced hypotension (Kalkan et al, 2004;Pentel et al, 1996;Tuncok et al, 2002;Kaplan et al, 2008). There are case reports suggesting the beneficial effects of vasopressin and glucagon in TCA overdose (Sensky and Olczak, 1999;Downes, 2003;Barry et al, 2006). Heard et al showed that TCA antibody fragments (TCA Fab) raise total serum TCA levels while lowering free levels in TCA-poisoned patients and no toxic effects were associated with the increase in TCA levels, but in this study, there were no significant changes in QRS duration, HR, or MAP associated with the Fab infusion (Heard et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Numerous case reports and laboratory investigations describe glucagon's effectiveness in reversing hypotension caused by overdoses of β-adrenergic blocking agents and calcium channel antagonists, although its mechanism of action would seem to make its effectiveness in calcium channel antagonists less likely than in overdoses from β-adrenergic blocking agents [101][102][103][104]. There are also reports of glucagon reversing TCA-induced hypotension [105,106]. In overdose patients, glucagon can be considered in hypotension unresponsive to the usual pressors (Level III recommendation).…”
Section: Vasoactive Agentsmentioning
confidence: 91%
“…40 mm Hg systolic rise after glucagon

Multiple drugs ingested in overdose.

Patient also received sodium bicarbonate, phenytoin and isoprenaline and fluid resuscitation

Cardiac rhythmNo response to 1 mg bolus glucagon. Broad complex reverted to sinus after 10 mg bolusSensky et al , 1999, UK9336-year-old OD admission. Toxicology dothiepin 2.58 mg/l, desmethyldothiepin 0.51 mg/l, paracetamol 135 mg/l, diazepam 0.33 mg/l, nordiazepam 0.12 mg/lCase reportBlood pressureNo response to 1 mg bolus glucagon.…”
Section: Relevant Papersmentioning
confidence: 99%